2013
DOI: 10.4028/www.scientific.net/amr.649.101
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Loudness of Sound Transmitted through Light Weight and Heavy Weight Walls

Abstract: When assessing the sound insulation quality of buildings constructions, policy makers and investors typically demand for single number ratings and sound insulation classes that allow for easy ranking of building products. Converting the full frequency content of a precisely measured or calculated structure into a single number, which takes into account all aspects of the insulation performance in a balanced way, is a challenging task. The recently proposed draft standard 717 proposes to take into account also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…In Rychtáriková et al, [3][4][5][6] a group of studies regarding the subjective perception of loudness in living environments are presented. The studies are based on rating noise types transmitted through lightweight and heavyweight wall structures, from now on denoted as LW and HW, respectively.…”
Section: Results: Associations Of Airborne Sound Data To Self-reportementioning
confidence: 99%
See 4 more Smart Citations
“…In Rychtáriková et al, [3][4][5][6] a group of studies regarding the subjective perception of loudness in living environments are presented. The studies are based on rating noise types transmitted through lightweight and heavyweight wall structures, from now on denoted as LW and HW, respectively.…”
Section: Results: Associations Of Airborne Sound Data To Self-reportementioning
confidence: 99%
“…In some cases, the participants reported that they would probably reply differently if the question of the test was to address the most annoying sound instead of the loudest one. 4 Specifically, in Rychtáriková et al, 3,4 a small sample of eight people rated 15 different sound stimuli of typical neighbor noise types (5 s each) filtered through a heavyweight wall (masonry) spectrum and a lightweight wall spectrum (gypsum boards on metal studs). 52 dB but different airborne SRI curves.…”
Section: Results: Associations Of Airborne Sound Data To Self-reportementioning
confidence: 99%
See 3 more Smart Citations